Early warning system: An urgent call for development and implementation of national consensus guidelines across the healthcare system of Pakistan - Nawaz, Qudsia (Pakistan Armed Forces Medical Journal, 2025)
The Editor, I am writing to highlight the urgent need for the implementation of a simple yet essential tool across the healthcare system of Pakistan: the Early Warning System (EWS). Vital signs are crucial indicators of general health and can predict both chronic disorders and acute deterioration in a patient’s condition. Monitoring these vital signs is a fundamental part of hospital care and observation. Early warning systems have evolved from vital signs charts, allowing for the early identification of patients at risk of serious deterioration before they collapse. These systems, tailored to patients’ clinical needs, such as maternal early warning systems and national early warning systems, are widely used in developed countries. They enable timely detection and intervention, preventing severe acute morbidity and mortality. This not only improves patient survival but also prevents the loss of millions of dollars in managing critically ill patients when it is already too late. Early detection boosts the morale of patients and their families and fosters trust in the healthcare system. Despite their proven benefits, early warning systems are not widely used in developing countries like Pakistan, where national guidelines for such systems are non-existent. As a result, healthcare professionals often rely on their personal knowledge and experience to determine when to alert specialist or intensivist care, leading to inconsistencies in patient care. There is a pressing need to establish national consensus guidelines for early warning systems in Pakistan. These guidelines should ensure that the EWS adopted nationwide is uniform, with similar triggers and only slight variations to cater to different physiological patient groups. Implementing such a system would bring significant improvements to our healthcare settings, leading to better patient outcomes and more efficient call management systems. I urge policymakers to prioritize the development and adoption of national guidelines for early warning systems. This will ensure that all healthcare professionals are aware of and can effectively use these systems, ultimately improving the quality and safety of healthcare in Pakistan. Sincerely, Dr. Qudsia Nawaz References: 1. Smith ME, Chiovaro JC, O’Neil M, Kansagara D, Quinones AR, Freeman M, et al. Early warning system scores for clinical deterioration in hospitalized patients: a systematic review. Ann Am Thorac Soc. 2014;11(9):1454-65. 2. Subbe CP, Kruger M, Rutherford P, Gemmel L. Validation of a modified Early Warning Score in medical admissions. QJM. 2001;94(10):521-6. 3. Gao H, McDonnell A, Harrison DA, Moore T, Adam S, Daly K, et al. Systematic review and evaluation of physiological track and trigger warning systems for identifying at-risk patients on the ward. Intensive Care Med. 2007;33(4):667-79. 4. Royal College of Physicians. National Early Warning Score (NEWS) 2: Standardising the assessment of acute-illness severity in the NHS. Updated report of a working party. London: RCP; 2017. 5. Alam N, Hobbelink EL, van Tienhoven AJ, van de Ven PM, Jansma EP, Nanayakkara PW. The impact of the use of the Early Warning Score (EWS) on patient outcomes: a systematic review. Resuscitation. 2014;85(5):587-94. 6. Ludikhuize J, Smorenburg SM, de Rooij SE, de Jonge E. Identification of deteriorating patients on general wards; measurement of vital parameters and potential effectiveness of the Modified Early Warning Score. J Crit Care. 2012;27(4):424.e7-13. 7. McNeill G, Bryden D. Do either early warning systems or emergency response teams improve hospital patient survival? A systematic review. Resuscitation. 2013;84(12):1652-67. 8. Kellett J, Sebat F. Make vital signs great again - A call for action. Eur J Intern Med. 2017;45:13-9. 9. Kyriacos U, Jelsma J, Jordan S. Monitoring vital signs using early warning scoring systems: a review of the literature. J Nurs Manag. 2011;19(3):311-30. 10. Morgan RJ, Williams F, Wright MM. An early warning scoring system for detecting developing critical illness. Clin Intensive Care. 1997;8(2):100. 11. Smith GB, Prytherch DR, Schmidt PE, Featherstone PI. Review and performance evaluation of aggregate weighted ’track and trigger’ systems. Resuscitation. 2008;77(2):170-9. 12. Jones DA, DeVita MA, Bellomo R. Rapid-response teams. N Engl J Med. 2011;365(2):139-46. 13. National Institute for Health and Care Excellence (NICE). Acutely ill adults in hospital: recognising and responding to deterioration. NICE clinical guideline 50. London: NICE; 2007. 14. Vincent JL, Einav S, Pearse R, Jaber S, Kranke P, Overdyk FJ, et al. Improving detection of patient deterioration in the general hospital ward environment. Eur J Anaesthesiol. 2018;35(5):325-33.